Prediction, analysis and estimation of factors affecting cardiac patients using regression models - Suhair Jameel Mushrif Al-Neyazy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The heart disease, myocardial infarction, heart failure, and stroke, in addition to high blood pressure, are among the most dangerous diseases for human life, as it may result in many complications that lead to death. Therefore, the study aimed to estimate a logistic regression model and predict the probability of heart disease, in addition to identifying the most important statistical methods in analyzing data of heart patients depending on the factors affecting their incidence (patient's gender, patient age, smoking, blood pressure).